Bank Profitability Analysis: the Role of Liquidity, Company Size, Asset Quality, and Leverage - Ulil Hartono; Desi Nurvitasari (MATRIK: JURNAL MANAJEMEN, STRATEGI BISNIS, DAN KEWIRAUSAHAAN, 2023)
Banks are one of the most important sectors for a country’s economic growth, so banks must be appropriatelymanaged. The success of bank management is reflected in resulting profitability. This research aims to analysethe effect of liquidity, firm size, asset quality, and leverage on bank profitability in 2017-2021. The populationin this study is 27, and the sample is 25, which was selected using purposive sampling. This study uses secondarydata from Bank financial reports obtained from the bank website. The result shows that liquidity and companysize did not affect profitability, while asset quality and leverage affected profitability. This research implies thatmanager banks must pay attention to asset quality and leverage by considering the 5C principle in assessingcreditworthiness.